Investigation of cross-platform realizations of stream symmetric ciphers - Kuznetsov, A.A.; Frolenko, V.O.; Eremin, E.S.; Ivanenko, D.V. (Radiotekhnika, 2018)
Modern symmetric stream ciphers Enocoro, Decim, Grain, HC, MUGI, Mickey, Rabbit, RC-4, Salsa20, SNOW2.0, Sosemanuk, Strumok, Trivium, and a block cipher AES, which can be used in streaming encryption modes, are being researched. The main results of testing the rate of formation of a key stream with cross-platform implementation of encryption algorithms in the Java programming language on operating systems Windows 10 (x64), Debian (Kali) and Android (x64) are presented. Testing was conducted on the portable personal computer (Intel Pentium 3550m 2.3GHz, RAM 4GB (1600МHz)) and on the mobile device, in particular, on the smartphone (Samsung galaxy S7).